Selection and identification of protective culture for controlling Staphylococcus aureus in fresh Domiati like cheese. Issue 1 (15th December 2017) - Ibrahim, Amel; Awad, Sameh
Abstract: Antibacterial activity of forty lactic acid bacteria (LAB) isolates toward Staphylococcus aureus was evaluated. The selected strains were then used as protective culture in artificial contaminated Domiati like cheese with S. aureus . The effect of using these strains on physicochemical properties and overall acceptability of fresh cheese was evaluated. Depending on its antibacterial activity, three strains of Lactobacillus rhamnosus 130RZFAAU, 131RZFAAU, and 190RZFAAU were selected for cheese making. No negative sensory properties were observed by the panelists when LAB strains were used as a single culture in the fresh cheese making. The application of these strains as protective culture in artificial contaminated cheesemaking process give a positive results. S. aureus was detected in cheese samples by culture method and propidium mono azide–quantitative polymerase chain reaction method. The results recommended that the strain L. rahmnosus 131RZFAUU that used in this study has antimicrobial activity against S. aureus and could be used as protective culture for improving the safety of Egyptian soft cheese. Practical applications: Detection of pathogenic bacteria by classical tests can take several days. It would be useful to have a rapid detection protocol to screen for the presence of Staphylococcus aureus in milk and cheese. Application of real‐time PCR in cheese is sufficient in characterization the S. aureus communities in raw milk and follow the dynamics of the entire populations in cheese. Recently, some scientific publications have shown that the naturally cheese microflora can efficiently prevent the growth of pathogenic or spoilage microorganisms. The control of spoilage and pathogens bacteria has been traditionally done by chemical additives, but the application of promising protective cultures, especially for traditionally cheeses made from raw milk, is limited. This work present some protective culture selected for controlling S. aureus in soft cheese. This work confirm the PMA‐q PCR method for detection live cells of S. aureus in cheese rapidly.